Konsep Diri Dan Kenakalan Remaja Pada Anak Jalanan - Helmita Asima Manalu; Doddy Hendro Wibowo (Jurnal Ilmiah Psyche, 2021)
The phenomenon of street children is a problem that has become a worldwide concern because of the increasing number. This study aims to determine the relationship between self-concept and juvenile delinquency in street children. This research was conducted in the city of Salatiga with the number of respondents as many as 34 teenagers with a quantitative descriptive approach. The sampling technique used is the technique Accidental Sampling. The results found in this study are the relationship between self-concept and juvenile delinquency in street children with a value obtained of -0.572 with a sig of 0.000. With this, that juvenile delinquency in street children is not a stand-alone situation but is a combination of several conditions experienced by street children, if a street child does not get direction from their parents and education, then delinquency in street children is a unavoidable problem.